Survival in patients with Amyotrophic Lateral Sclerosis - Melissa Serra Ruíz; Miguel Angel Serra Valdes (Universidad de Ciencias Médicas de La Habana, 2019)
Introduction. Amyotrophic lateral sclerosis (ALS) is the most frequent disease in the heterogeneous group of disorders with motor neuron diseases. Objective: To characterize the survival of patients diagnosed with amyotrophic lateral sclerosis considering factors related to their clinical behavior at "Dr. Jose Rafael Estrada Gonzalez" National Institute of Neurology and Neurosurgery, Havana, Cuba. Material and Methods: A descriptive and retrospective research was conducted.  The study included a case series of 147 patients diagnosed with ALS by clinical and neurophysiological confirmation and images. The patients were treated in the multidisciplinary consultation in the period from October 2005 to October 2015.  A total of 110 of them already died. Results: The disease most often occurs between the ages of 51 and 60. In the first 40 months, most of the patients in the series died, for a total of 80 people. The spinal clinical form predominated in males who had higher survival; the bulbar form prevailed in women. Most of the patients had no risk factors. Diabetes, arterial hypertension, ischemic cerebrovascular disease, neoplasms, hepatitis C, head trauma, bronchial asthma and ischemic heart disease stand out as comorbidities.  There were cases of the disease within a single family. Conclusions The greatest survival from the diagnosis of the disease was observed in the group between 51 and 60 years of diagnosis of the disease, some of them reaching up to 10 years. The general average of survival was between 2 and 5 years.  It was lower in patients with comorbidities, family history and bulbar form. After evaluating the effectiveness of the treatment with Riluzole, the survival was not significant.  Keywords: amyotrophic lateral sclerosis, motor neuron disease, survival, risk factors, clinical forms, mortality, Riluzole.